[C5H12N]2SnBr6: a lead-free phase transition compound with switchable quadratic nonlinear optical properties. (28th February 2023) - Hu, Xinxin; Xu, Haojie; Guo, Wuqian; Han, Shiguo; Liu, Yi; Ma, Yu; Fan, Qingshun; Luo, Junhua; Sun, Zhihua
Abstract : We reported a lead-free phase transition compound that enables reversible switching of quadratic nonlinear optical properties. Abstract : Solid-state phase transition materials with tunable quadratic nonlinear optical (NLO) properties under different states hold great potential applications in a wide range of fields. Despite great efforts, lead-free organic–inorganic hybrid NLO switchable materials are still scarce. Here, we report a new lead-free organic–inorganic hybrid compound (NMP)2 SnBr6 (1, where NMP is N -methylpyrrolidinium) which adopts the zero-dimensional perovskite-like motif. It demonstrates a structural phase transition at T c = 352 K, as confirmed by differential scanning calorimetry and specific heat measurements. Single-crystal structure analyses at different temperatures indicate the occurrence of symmetry breaking from Pbam (at 360 K, > T c ) to Pba 2 (at 300 K, < T c ), which can be attributed to the configuration changes of organic N -methylpyrrolidinium cations. In particular, 1 shows remarkable NLO signal contrast up to ∼25 and excellent switching stability after multiple heating–cooling cycles, suggesting its potential application as a switchable NLO material. This work paves the way for exploring new organic–inorganic hybrid functional materials.